2019
DOI: 10.1002/ijc.32530
|View full text |Cite
|
Sign up to set email alerts
|

FRK plays an oncogenic role in non‐small cell lung cancer by enhancing the stemness phenotype via induction of metabolic reprogramming

Abstract: The role of Fyn‐related kinase (FRK) in malignant tumors remains controversial. Our study investigated the function of FRK in lung cancer. Immunohistochemistry staining and generating a knockout of FRK by CRISPR/Cas9 in H1299 (FRK‐KO‐H1299) cells were strategies used to explore the role of FRK. Immunohistochemistry staining indicated that FRK expression was elevated in 223 lung cancer tissues compared to 26 distant normal lung tissues. FRK contributed to poor survival status in lung cancer patients and acted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…At present, the malignant phenotype of most tumor tissues is closely related to the metabolisms of special material and energy, such as oral cancer (Nakazato et al 2019), hepatocellular carcinoma (Fang et al 2019), pancreatic cancer (Yang et al 2019), non-small cell lung cancer (Zhang et al 2019), prostate cancer (Marin de Mas et al 2019), etc. Colorectal cancer (CRC) is the most frequent malignant gastrointestinal tumor and a leading cause of cancer death worldwide, along with an increase of about 150,000 cases every year (Jemal et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the malignant phenotype of most tumor tissues is closely related to the metabolisms of special material and energy, such as oral cancer (Nakazato et al 2019), hepatocellular carcinoma (Fang et al 2019), pancreatic cancer (Yang et al 2019), non-small cell lung cancer (Zhang et al 2019), prostate cancer (Marin de Mas et al 2019), etc. Colorectal cancer (CRC) is the most frequent malignant gastrointestinal tumor and a leading cause of cancer death worldwide, along with an increase of about 150,000 cases every year (Jemal et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al found that A549 cells secrete SEMA3A to inhibit the maturation and functions of dendritic cells, which might be associated with the unidenti ed mechanism of immune evasion by tumor cells [52]. Interestingly, FRK was considered to be a underlying treatment target for drug discovery, as it has a carcinogenic effect in lung cancer cells via inducing metabolic reprogramming and nally promoting epithelial-mesenchymal transition and metastasis [53]. TOMM6 is an upregulated mRNA-related lncRNA UCA1 that might affect cisplatin resistance in LUAD [54].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, in yet another sarcoma study, complete knockout of ORF57 was achieved in iSLK/Bac16 and HEK293/Bac36 cells, simultaneously expressing one Cas9 protein and two guide RNAs associated by several rounds of single-cell cloning and cell selection from a single vector [ 30 ]. In a further trial, researchers investigated the role of the FRK oncogene in the H1299 lung cancer cell line, demonstrating that knockout of FRK suppressed epithelial to mesenchymal transition cell colony formation and proliferation of cancer cells [ 31 ]. In turn, in a study concerning canine cancer research, knockout of one of the main tumor suppressor genes, TP53, was rescued by administration of TP53 gRNA, resulting in in vivo and in vitro non-cancerous phenotypes [ 32 ].…”
Section: Applications and Advances Of The Crispr/cas9 Technique Inmentioning
confidence: 99%